The Application of Magnetic-Controlled Capsule Gastroscopy in Patients Refusing C-EGD: A Single-Center 5-Year Observational Study - Lihan Zhou; Sijia Wang; Jian Li; Jie Zhong; Ling Zhang; Ruizhe Shen; Bielike Kouken; Chunhua Zhou; Qi Wang; Yuting Qian; Duowu Zou; Ye Chu (Gastroenterology Research and Practice)
Background and Aims. Screening for gastric diseases in symptomatic outpatients with conventional esophagogastroduodenoscopy (C-EGD) is expensive and has poor compliance. We aimed to explore the efficiency and safety of magnetic-controlled capsule gastroscopy (MCCG) in symptomatic outpatients who refused C-EGD. Methods. We performed a retrospective study of 76794 consecutive symptomatic outpatients from January 2014 to October 2019. A total of 2318 adults (F/M=1064/1254) in the MCCG group who refused C-EGD were matched with adults in the C-EGD group using propensity-score matching (PSM). The detection rates of abnormalities were analyzed to explore the application of MCCG in symptomatic patients. Results. Our study demonstrated a prevalence of gastric ulcers (GUs) in patients with functional dyspepsia- (FD-) like symptoms of 8.14%. The detection rate of esophagitis and Barrett’s esophagus was higher in patients with typical gastroesophageal reflux disease (GERD) symptoms than in patients in the other four groups (P<0.01). The detection rates of gastric ulcers in the five groups (abdominal pain, bloating, heartburn, follow-up, and bleeding) were significantly different (P=0.015). The total detection rate of gastric ulcers in symptomatic patients was 9.7%. A total of 7 advanced carcinomas were detected by MCCG and confirmed by endoscopic or surgical biopsy. The advanced gastric cancer detection rate was not significantly different between the MCCG group and the C-EGD matched group in terms of nonhematemesis GI bleeding (2 vs. 2, P=1.00). In addition, the overall focal lesion detection rate in the MCCG group was superior to that in the C-EGD matched group (224 vs. 184, P=0.038). MCCG gained a clinically meaningful small bowel diagnostic yield of 54.8% (17/31) out of 31 cases of suspected small bowel bleeding. No patient reported capsule retention at the two-week follow-up. Conclusion. MCCG is well tolerated, safe, and technically feasible and has a considerable diagnostic yield. The overall gastric diagnostic yield of gastric focal lesions with MCCG was comparable to that with C-EGD. MCCG offered a supplementary diagnosis in patients who had a previously undiagnostic C-EGD, indicating that MCCG could play an important role in the routine monitoring and follow-up of outpatient. MCCG shows its safety and efficiency in symptomatic outpatient applications.